Research Progress of External Ventricular Drainage Catheterization Techniques - Zhenzhen HAN; Kunshan YUAN; Haijun ZHANG (Zhongguo yiliao qixie zazhi)
Insertion of external ventricular drainage (EVD) is an effective neurosurgical treatment approach. The accuracy of EVD insertion is related to potential complications, and the precise placement of the catheter tip can reduce the incidence of complications. With the progress of medical technology, the research and application of EVD catheterization technology are developing rapidly. This paper reviews the traditional blind catheterization, computed tomography, ultrasound guidance, mixed reality navigation system, laser positioning neural navigation, mobile device neural navigation, stereotactic system, and the visualization technology of the whole process of neuroendoscope assisted ventricle puncture to guide EVD catheterization to provide references for clinical decision-making by medical staff.